Effect of a 48-Hour Thickened Liquid Protocol on Visuospatial Skills in Young Adults. - Thompson, Elizabeth; Gorham-Rowan, Mary; Carter, Matthew D.; Lamb, Katherine M. (Folia Phoniatrica et Logopaedica, 2025)
Introduction: Thickened liquids are frequently recommended for individuals with swallowing disorders who are at risk of aspiration. However, thickened liquids may be poorly tolerated and result in reduced fluid intake, which may impact performance in a number of areas. The purpose of this study was to examine the possible impact of a thickened liquid regimen on visuospatial skills in young healthy adults. Methods: Twenty young adults, aged 19–26 years, were included as participants. Baseline data consisting of urine specific gravity (USG) measurements as a marker of hydration status and completion of a visuospatial task were obtained prior to initiation of the experimental protocol. Participants in the experimental group followed a thickened liquid protocol, which consisted of drinking nectar-thick liquids for 48 h. Data collection procedures were repeated. Results: Participants in the experimental group exhibited significantly higher USG levels and required more time to complete the visuospatial task post-thickened liquids. No significant change in performance accuracy was found. Participants in the experimental group reported a decrease in fluid intake. Conclusion: Performance accuracy on a visuospatial task was not significantly impacted by a 48-h period of thickened liquid intake, but time required to complete the task increased and was associated with mild dehydration as indicated by higher USG levels.